Managing Cashew Rootstock Grafting Size Through Organic Fertilizers - Langa, Rogério; Cambule, Armindo; Jorge, Felicidade; Uaciquete, Américo; Barros, Gabriel; Ferreira, Neid Ali (Journal of Agricultural Studies, 2021)
Seed born cashew (Anacardium occidentale L) seedlings are planted directly when they are produced from polyclonal orchards. In a common scenario, cashew seedlings are grafted before transplanting. For this purpose, adjusting the size between scions and rootstock is highly important for the success of grafts and it can be achieved through a visual selection of scions. However, when working with large numbers of seedlings physical and visual selection becomes laborious and time consuming for the workers. Therefore, creating uniformity in seedlings size before grafting is crucial. We present experimental results showing the linear regression between the fertilization level and seedling stem size. Two experiments were conducted in Mozambique: One at Nassuruma cashew Research Station, Nampula province, following a Completely Randonmized Block Design (CRBD), seven treatments, ten bags per treatment and five replicates. The treatments consisted of a fertilizer organically composted from cashew nut shells and applied at rates of 0, 4, 8, 16, 32, 40 and 48% of the total amount of soil in each bag. The second experiment was carried out at Chizavane nursery, in Gaza Province, also based on CRBD, in factorial arrangement of 4 and 3 levels of Kelp and Stimu biofertilizers respectively. Two stem size variables, diameter and height, were considered and data collected at 120 days after seedlings emergence in Nampula and 45 days after emergence in Gaza Province. Polynomial or simple regression analysis model for stem diameter and plant height was performed. The stem diameter was linearly described as an increasing equation. The height was also linearly related to fertilizer but following a decreased equation. We concluded that applying appropriate dosage of fertilizer in the soil or on the leaves could adjust the stem size of the rootstock required for grafting and therefore adjust the stem to the size of scions available. The treatments with high level of Kelp, Stimu and cashew compost fertilization resulted in increase of 8,5%, 6% and 16,6% of diameter respectively. However, the treatments caused a reduction of height at rate of 14,3%, 3,2% and 25,08% respectively. The stem and scion size adjustment are highly important for increasing the grafting success rate in a cashew nursery.